2023
DOI: 10.1021/jacs.2c09937
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Templated Glycopolymer Nanopatterns Transferred to Hydrogels for Designed Multivalent Carbohydrate–Lectin Interactions across Length Scales

Abstract: Multivalent interactions between carbohydrates and proteins enable a broad range of selective chemical processes of critical biological importance. Such interactions can extend from the macromolecular scale (1−10 nm) up to much larger scales across a cell or tissue, placing substantial demands on chemically patterned materials aiming to leverage similar interactions in vitro.Here, we show that diyne amphiphiles with carbohydrate headgroups can be assembled on highly oriented pyrolytic graphite (HOPG) to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Previously, we have shown that the sPDA layers on HOPG can be transferred to soft materials including PDMS , and hydrogels, , taking advantage of the cross-linking reactions used to solidify the bulk polymer (Figure a). For instance, in polyacrylamide (PAAm) hydrogel cross-linking, the free radical polymerization reaction can utilize the PDA as a reactant, which creates a covalent linkage between the PAAm and the sPDA layer.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that the sPDA layers on HOPG can be transferred to soft materials including PDMS , and hydrogels, , taking advantage of the cross-linking reactions used to solidify the bulk polymer (Figure a). For instance, in polyacrylamide (PAAm) hydrogel cross-linking, the free radical polymerization reaction can utilize the PDA as a reactant, which creates a covalent linkage between the PAAm and the sPDA layer.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between alkyl chains of phospholipids and HOPG is stronger than phospholipid molecule–molecule interactions. The Claridge research group’s series of studies utilized phospholipids as a surface chemical modification material for two-dimensional materials. Through the Langmuir method, diyne PE and diyne PC established strips on the MoS 2 or HOPG. Subsequently, it was proved that the phospholipid strips were more stable after being ultraviolet polymerized .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that it is possible to generate nm-scale chemical patterns in the surface chemistry of PDMS and other soft materials. , Functionalization starts by assembling striped phases of diacetylene (DA)-modified amphiphiles on highly oriented pyrolytic graphite (HOPG). In the striped phases, the alkyl chain of the amphiphile lies flat on the HOPG substrate (Figure a), generating 1 nm-wide stripes of paired functional headgroups embedded in a stripe of exposed alkyl chains. Photopolymerization of aligned DA groups (Figure a, bottom) produces polydiacetylene (PDA) backbones that tether together molecules within the layer.…”
Section: Introductionmentioning
confidence: 99%